UPAYA PENCEGAHAN STUNTING MELALUI PROGAM PEMBERDAYAAN GERAKAN MAKAN TINGGI PROTEIN HEWANI DI KB PUCANGSAWIT SURAKARTA - Madhan, Nuvaisha Nur; Purwanto, Danang (FISIP Universitas Malikussaleh, 2025)
This study aims to explore how the empowerment process is implemented through the Gerakan Makan Tinggi Protein Hewani (GEMATI) program as an effort to prevent stunting in Kampung Pucangsawit. The research employs a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The theoretical framework used is the community empowerment theory proposed by Kartasasmita, which consists of three key aspects: Enabling, Empowering, and Protecting. The Enabling aspect emphasizes the creation of conditions that allow the community to develop their potential; the Empowering aspect focuses on strengthening the capacities the community already possesses; and the Protecting aspect highlights the importance of protection and assistance throughout the process. The results of this study indicate that the interventions carried out through the GEMATI program have not yet been fully optimal in preventing and addressing stunting. Overall, the findings suggest that various factors influence the success of the empowerment process. Stunting prevention cannot rely solely on nutritional improvement, but also depends on other elements such as economic status, environmental conditions, and community behavior. Numerous interventions that have been implemented will not achieve optimal outcomes without concurrent improvements in these supporting factors. Therefore, full participation and collaboration across all sectors are essential to achieving the desired goals.